Profil et compétences des traducteurs/traductrices des départements de langues espagnole et française de la Direction générale de la traduction. - Le Poder, Marie-Evelyne (The Journal of Specialised Translation, 2014)
This article consists of a study of the profiles and the skills of the translators of the Departments of Spanish and French who work at the Directorate-General for Translation (Translation DG) in Brussels. Further to a professional internship within the Translation DG of the European Commission, field work based on structured interviews was performed with translators of these Departments. After a brief introduction, we present the theoretical framework of our study (literature review and theoretical basis chosen). Then we present our hypothesis and objectives. Finally, we describe the methodology we have used before analysing the results obtained.